Coping with Scarcity: a Comparison of Dearth Policies in Three Regions in Northwestern Europe in the Fifteenth and Sixteenth Centuries. - Dijkman, Jessica (TSEG - The Low Countries Journal of Social and Economic History, 2018)
This article compares dearth policies developing in three regions in northwestern Europe in the fifteenth and sixteenth centuries: East Anglia, coastal Picardy and Upper Normandy, and Holland. Based on a survey of existing research, it examines the reactions of authorities to food crises and the factors shaping these reactions. Two elements of dearth policy are investigated: restrictions on the grain trade on the one hand, and public grain stocks on the other. The article shows how social, political and economic characteristics of each region affected the way in which the authorities attempted to manage food crises, but also demonstrates that the exigencies of dearth were strong enough to partly overcome differences.